Protection Towards Cultural Heritage in Armed Conflict: A Comparative Study of Islam and Christianity - Chafrina, Gracella; Hendri, Vernanda Jessica; Wijayawati, Stephani; Ridhanti, Alya Nabila (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Analysis: Islamic and Christian Perspectives on Cultural Heritage Protection. Research Objective: This study aims to provide a comprehensive examination of challenges in articulating ethical approaches to heritage preservation within Islamic and Christian contexts, exploring how religious teachings inform cultural protection frameworks. Research Method: The research employed doctrinal methodology, analyzing religious teachings from Islamic jurisprudence sources and Christian ecumenical council doctrines to understand each tradition's perspective on cultural heritage protection and preservation ethics. Results: The investigation reveals that neither the Quran nor the Bible explicitly mandates cultural heritage protection. However, Islamic teachings through the Prophet Muhammad's traditions emphasize respect and conservation of cultural heritage. Christian denominations following ecumenical councils adopt liberal approaches, viewing heritage protection as preserving liturgical truth, divine concepts, and sacred icons. Findings and Implications: The study identifies dual challenges: Islam faces difficulties in comprehensively capturing phenomena and confronts existing biases in heritage preservation studies, while Christianity demonstrates more flexible interpretations linking heritage protection to spiritual preservation. These findings suggest both religions provide implicit ethical foundations for cultural heritage protection. Conclusion: While cultural heritage protection constitutes customary international law and war crimes under the Rome Statute, Islamic and Christian perspectives offer distinct yet supportive ethical frameworks for preservation efforts, contributing valuable religious dimensions to international protection discourse. Contribution: This research contributes comparative theological analysis to heritage studies, bridging religious ethics with international cultural protection frameworks and addressing gaps in religion-based preservation approaches within contemporary scholarship. Limitations: The study restricts analysis to two major religions and relies solely on doctrinal methodology, potentially overlooking practical implementations and contemporary challenges in heritage protection applications. Suggestions: Future research should expand to include additional religious perspectives, integrate empirical methodologies examining practical applications, and develop comprehensive frameworks addressing identified biases while exploring concrete case studies of religious principles in cultural protection contexts